Reaktualisasi Politik Demokrasi: Politik Agensi dan Revitalisasi Kelembagaan Demokrasi - Trijono, Lambang (Jurnal Ilmu Sosial dan Ilmu Politik, 2011)
Democratic crisis which has experienced by Indonesia recently has happened partly due to the weakening of the effectiveness of political parties and representative institutions in representing public interests. Both institutions are more involved in internal issues rather than focusing on public interests. As a result, the public trust toward the institutions which are also the pillar of democracy is declining drastically in recent years. This article underlines the establishment of a new political discourse through the development of agonistic political model which the author believed to be more effective in representing public interests and activating political institutions to perform its functions.